Tranquillity and Soundscapes in Urban Green Spaces—Predicted and Actual Assessments from a Questionnaire Survey. (February 2013) - Watts, Greg; Miah, Abdul; Pheasant, Rob
A previous pilot study demonstrated the utility of a tranquillity prediction tool TRAPT for use in three green open spaces in a densely populated area. This allows the calculation of perceived levels of tranquillity in open spaces. The current study expands the range of sites to eight and, importantly, considers the views of visitors to these spaces. In total 252 face-to-face interviews were conducted in these spaces. An important aim of the survey was to determine the extent to which reported tranquillity obtained from the questionnaire survey could be predicted by a previously developed prediction tool TRAPT. A further aim was to determine what other factors may need to be considered in addition to the purely physical descriptors in TRAPT. The questions included the sounds and sights that were noticed, factors affecting tranquillity, as well as questions related to the benefits of visiting these areas. Predictions were considered satisfactory and could be improved further by taking account of issues surrounding personal safety. Examining the trends in these data, it was also shown that the percentage of people feeling more relaxed after visiting the spaces was closely related to overall assessments of perceived tranquillity. Further trends and their implications are presented and discussed.